2004
DOI: 10.4141/a03-103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheat cultivar and enzyme supplementation on nutrient availability and performance of laying hens

Abstract: Rafuse, J. L., Silversides, F. G., Bedford, M. R. and Simmins, P. H. 2004. Effect of wheat cultivar and enzyme supplementation on nutrient availability and performance of laying hens. Can. J. Anim. Sci. 84: 397-402. This study examined the effect of four wheat cultivars (Belvedere, Glenlea, Norboro, and Walton) grown in the Maritime provinces of Canada and dietary enzyme supplementation on apparent metabolizable energy (AME), digestibility of crude protein (CP), and performance of laying hens, and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, as expected, egg yolk colour was markedly lower than that normally reported for laying hens consuming maize-based diets (Pérez-Bonilla et al, 2012;Li et al, 2013). Similar to the results of the present study, Rafuse et al (2004) observed that diets based on wheat with a mixture of xylanase and protease did not affect albumen height, yolk weight, eggshell weight or albumen weight when measured three weeks (32 weeks old) after the hens began to consume the experimental diets. In addition, as in the present experiment, Boling et al (2000) showed that feeding diets containing 1.0 g NPP/kg, 1.5 g NPP/kg or 4.5 g NPP/kg without or with phytase supplementation had no effect on specific gravity.…”
Section: Discussionsupporting
confidence: 89%
“…However, as expected, egg yolk colour was markedly lower than that normally reported for laying hens consuming maize-based diets (Pérez-Bonilla et al, 2012;Li et al, 2013). Similar to the results of the present study, Rafuse et al (2004) observed that diets based on wheat with a mixture of xylanase and protease did not affect albumen height, yolk weight, eggshell weight or albumen weight when measured three weeks (32 weeks old) after the hens began to consume the experimental diets. In addition, as in the present experiment, Boling et al (2000) showed that feeding diets containing 1.0 g NPP/kg, 1.5 g NPP/kg or 4.5 g NPP/kg without or with phytase supplementation had no effect on specific gravity.…”
Section: Discussionsupporting
confidence: 89%
“…Roberts & Choct (2006) reported that enzyme supplementation improved eggshell breaking strength in hens fed wheat-based diets. In contrast, Rafuse et al (2004) observed that diets based on wheat with a mixture of xylanase and protease did not affect albumen height, or weight of yolk, eggshell and albumen when measured 3 wk (32 wk of age) after the hens began consuming the experimental diets. Likewise, Çiftci et al (2003a) reported no effect on eggshell thickness when 30% corn was substituted by wheat in diets for SCWL hens from 27 to 43 wk of age.…”
Section: Discussionmentioning
confidence: 80%
“…However, there was a significant effect of dietary treatments on the Haugh unit between some wheat cultivars on week 67. Rafuse et al (2004) also reported no significant influence of dietary wheat cultivars and supplemental enzymes on egg quality traits in hens. In the present study, eggshell weight (%) was higher in the layers fed with the enzyme-supplemented diets, including (week 67 of age).…”
Section: Egg Quality Traitsmentioning
confidence: 96%
“…Decreased EP in laying hens fed diets with high levels of NSPs with supplemental enzyme was reported during 25-28 weeks of age (Nguyen et al, 2021). Rafuse et al (2004) examined the effect of four Canadian wheat varieties with or without enzyme on the performance of laying hens and reported no significant effect of the experimental diets on EP, FCR and EW. In contrast, a significant decrease in EW and EM with no significant effect on EP were observed in the research study with increasing levels of dietary wheat (Mirzaie et al, 2012), but supplementing diets with xylanase improved EM, EP and FCR.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation